Variability of recurrence interval and single-event slip for surface-rupturing earthquakes in New Zealand. Issue 1 (2nd January 2016) - Nicol, A; Robinson, R; Van Dissen, RJ; Harvison, A
ABSTRACT: Recurrence interval (RI) and single-event slip (SES) for large-magnitude earthquakes that ruptured the ground surface ( M w > 6–7.2) can vary by more than an order of magnitude on individual faults. Frequency histograms, probability density functions (PDFs) and coefficient of variation ( C v, standard deviation/arithmetic mean) values for geological and simulated earthquakes on over 100 New Zealand active faults have been used to quantify RI and SES variability. Histograms of RI and SES for geological paleoearthquakes were constructed using a Monte Carlo method which accounts for the observations and their uncertainties. For the best of the geological PDFs (i.e. ≥7 surface-rupturing events) and earthquake simulations, RI are positively skewed with long recurrence tails (c. three times the mean) which are approximately described by log-normal and Weibull distributions. The geometric mean and coefficient of variation ( C vln ) calculated for these log-normal distributions may be up to a factor of two lower and higher, respectively, than those determined assuming a normal distribution. By contrast, SES for geological and simulated earthquakes is often approximately normally distributed and appears to be less variable than RI (RI C v 0.6 ± 0.2 geological and 0.6 ± 0.3 simulations; SES C v 0.4 ± 0.2 geological). Variations in earthquake RI and to a lesser extent SES produce order-of-magnitude changes in slip rate over time intervals up to five times the arithmetic mean RI. Quantifying variability of RI, SES and slip rates is important when producing estimates of seismic hazard for surface-rupturing earthquakes, and could be estimated for active faults with poorly constrained paleoearthquake histories using the PDFs presented here.